Evaluation of growth and reproductive performance of Borana cattle and their crosses with Friesian at Abernossa, Shoa, Ethiopia - Hailemariam, M. (1987)
Data collected between 1977 and 1985 on reproductive and growth traits of Borana cattle and their crosses with Friesian, were analysed using the least-squares procedure. The animals were maintained for beef and in-calf dairy heifer production at the Abernossa Cattle Breeding and Improvement Ranch of the Ministry of Agriculture. The result of the analysis showed that the mean number of services per conception for first pregnancy was 1.701. The difference among the breed groups was not significant but both year and season of conception had significant influence. Heifers, which conceived during the small rainy and dry seasons, required 0.16 and 0.21 more services, respectively, than those conceiving during the big rainy season. Age at first calving (AFC) averaged 31.5, 32.7, 45.2 and 46.8 months for F1, 3/4 Friesian, Boran mated to Boran bulls and artificially inseminated Boran heifers, respectively. Year of birth had a significant effect on AFC of all mating groups except on that of artificially inseminated Boran heifers. Season of birth had significant effect on AFC of Fl heifers only. The mean values for calving interval (CI) were 465, 552, 525 and 437 days respectively for Boran cows mated to Boran bulls, Boran cows mated to Friesian bulls, Boran cows artificially inseminated and Fl cows artificially inseminated. Year of calving had a significant effect on CI of all cow mating groups but influence of season was significant on Boran cows mated to Boran bulls and Boran cows artificially inseminated only. Parity had signficant influence on CI of all Boran dams, but not on F1 dams. The preweaning mortality rate was 4.0% and 2.9% for Borana and Fl cross calves, respectively. Parity of dam, sex of calf and the interaction between breed group of calf and year of birth were significant. The total mortality rate up to first calving age for pure Boran cattle was estimated to be 11.5%. Based on this a cow in Boran Breeding unit needed 2.27 calvings to produce a heifer calf that could in turn calve in the herd. Thus, 37 percent of the females born were required as herd replacements, and the generation interval was 6.6 years. Mean body weight of Boran, Fl and 3/4 Friesian cross calves was 25.17 kg, 25.39 kg and 25.73 kg at birth and 157.5 kg, 176.7 kg and 179.9 kg at weaning, respectively. All factors included in the analysis and their interaction had a significant effect on both parameters with the exception of the effect of season of birth and its interaction with breed group on birth weight. Weights of Boran calves at one-, two- and three-years of age were 179 kg, 269 kg and 338 kg, respectively. Sex and year of birth had significant effect on weights at these three stages. Season of birth had a significant effect on the two-year weight while the effect of parity of dam was significant on the one-year weight only. Estimated heritability values of 0.32, 0.24, 0.43, 0.29 and 0.24 for birth, weaning, one-year, two-year and three-year weights of Boran cattle suggest that body weight increase of 0.11. 1.1, 2.8, 3.1 and 2.4 kg per year could be achieved through selection at the respective ages. Cow productivity index of 127 kg and 122 kg of an eight-month old weaner calf per cow per year was estimated for Boran cows weaning Boran and F1 calves, respectively. Cow productivity of all cows was significantly influenced by year of calving and parity of dam. Boran cows producing F1 calves were more productive when calving during the small rainy season than those calving during the other seasons.